A Study on Features of Different Tone Quality in a Kenong Set - Ahmad Faudzi, Musib; Sinin, Hamdan; Saiful Hairi, Othman (Universiti Putra Malaysia (UPM) Press, 2023)
This work discusses how to distinguish kenong frequencies in a signal and the timelocalized frequency content for each tone at a given time using an audio-based approach to tuning retrieval where the fundamental and overtone pitch is shown at all frequencies at a given time. The method of temporal localization on the dominant frequency at its unique time for each tone allows for the detection of frequencies present in the signal. Two approaches used in retrieving the harmonic, pitch, and timbre of kenong are Picoscope and Melda analyzer. The audio recording was done using an At4050 microphone and Ur22 audio interface in mono at 24-bit resolution and 48 kHz sampling rate. PicoScope produces the spectrum while the Melda analyzer produces changes in the spectra with time. Kenong D, E, G, A, and C displayed their near overtones at (2:2.8:4.0), (2:3.0:3.9), (2:2.9:3.9), (2:2.6:3.9), and (2:2.6:3.9). Kenong D had a strong fundamental peak at 295Hz. Kenong G keeps the fundamental frequency constant until t=5s. The basic peak was maintained by Kenong C. The results reveal that the kenong was properly tuned, although the tuner solely tuned it based on hearing, passed down from generation to generation. The maker’s intuition permits him to create a specific ‘signature’ through sound unique to a given kenong set.